1974
DOI: 10.1901/jaba.1974.7-427
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Generalized Correct Social Contingencies: An Evaluation of a Training Program1

Abstract: Two aides operating a kindergarten-style program for institutionalized mental retardates were trained, using observer feedback, to apply generalized "correct" social contingencies to 10 defined classes of appropriate and inappropriate child behaviors. A multiple baseline design was used to demonstrate, sequentially, the effects of the training procedure upon the attending behavior of each teacher. After withdrawal of feedback, a posttraining follow-up served to assess the durability of training. For both aides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Feedback has been used with process information only (e.g., Guercio et al, 2005;Hutchison, Jarman, & Bailey, 1980;Montegar, Reid, Madsen, & Ewell, 1977;Parsonson, Baer, & Baer, 1974;Welsch, Ludwig, Radiker, & Krapfl, 1973;Wilson, Reid, & Korabek-Pinkowski, 1991), outcome only (e.g., Lattimore, Stephens, Favell, & Risley, 1984;Quilitch, 1975), or both (e.g., Arco, 1997;Greene, Willis, Levy, & Bailey, 1978;Huberman & O'Brien, 1999;Korabek, Reid, & Ivancic, 1981;Mozzoni & Bailey, 1996;Parsons, Cash, & Reid, 1989;Prue, Krapfl, Noah, Cannon, & Maley, 1980;Schepis & Reid, 1994). However, if the purpose of staff training is to produce specific client outcomes such as increased independent self-care or less problem behavior, then it makes sense to combine process and outcome feedback, particularly in the initial stages of training during which the functional interactions between staff and client behavior need to be seen and experienced (see Earley, Northcraft, Lee, &Lituchy, 1990, andKim, 1984, who showed beneficial effects of combining process with outcome feedback in nonclinical settings).…”
Section: Training (Stage 2): Combining Supervisory Feedback With Selfmentioning
confidence: 99%
“…Feedback has been used with process information only (e.g., Guercio et al, 2005;Hutchison, Jarman, & Bailey, 1980;Montegar, Reid, Madsen, & Ewell, 1977;Parsonson, Baer, & Baer, 1974;Welsch, Ludwig, Radiker, & Krapfl, 1973;Wilson, Reid, & Korabek-Pinkowski, 1991), outcome only (e.g., Lattimore, Stephens, Favell, & Risley, 1984;Quilitch, 1975), or both (e.g., Arco, 1997;Greene, Willis, Levy, & Bailey, 1978;Huberman & O'Brien, 1999;Korabek, Reid, & Ivancic, 1981;Mozzoni & Bailey, 1996;Parsons, Cash, & Reid, 1989;Prue, Krapfl, Noah, Cannon, & Maley, 1980;Schepis & Reid, 1994). However, if the purpose of staff training is to produce specific client outcomes such as increased independent self-care or less problem behavior, then it makes sense to combine process and outcome feedback, particularly in the initial stages of training during which the functional interactions between staff and client behavior need to be seen and experienced (see Earley, Northcraft, Lee, &Lituchy, 1990, andKim, 1984, who showed beneficial effects of combining process with outcome feedback in nonclinical settings).…”
Section: Training (Stage 2): Combining Supervisory Feedback With Selfmentioning
confidence: 99%
“…Behavioral research has increasingly focused on developing training procedures that facilitate the generalization of targeted skills to different behaviors, settings, individuals, and times (Koegel, Glahn, & Nieminen, 1978; Koegel, Russo, & Rincover, 1977;Parsonson, Baer, & Baer, 1974). Evidence from the parent training field indicates that parents do not necessarily apply their skills to other untreated problem behaviors, other siblings, new settings, or when therapist contact terminates (e.g., Forehand & Atkeson, 1977;Miller & Sloane, 1976;O'Dell, Flynn & Benlolo, 1977;Patterson, 1974;Rosenthal, 1976).…”
mentioning
confidence: 99%
“…Previous research has demonstrated that individuals can be taught to apply experimenterdesigned procedures and, perhaps, to generalize the use of these procedures to new situations (Gladstone & Sherman, 1975;Koegel, Glahn, & Nieminen, 1978;Koegel et al, 1977;Parsonson et al, 1974). The present experiment differed from these studies in its aim to instruct teachers to write as well as to implement behavior modification programs.…”
Section: Discussionmentioning
confidence: 91%
“…After instruction, teachers may be able to apply the trained procedures to new situations (Koegel, Russo, & Rincover, 1977) and continue using the procedures over time (Parsonson, Baer, & Baer, 1974).…”
mentioning
confidence: 99%